Bisnis Digital: Studi Kasus Penggunaan VTube, Jempol Preneur, dan Goins di Masa Pandemi Covid-19 - Rifqiani Nur Fadhillah (Emik, 2021)
The Covid-19 pandemic has not only created social fear, but has also affected various aspects of human life, including in the field of economy. To reduce the spread of Covid-19, the government issued a work from home (WFH) policy and study from home. This not only limits the interaction between people, but this condition also causes people to be creative and look for alternatives to earn income. One that has the potential to be done is a digital business, which is not only easy and simple (using gadgets and internet networks), but can also be done anywhere, especially at home because of the "stay at home" policy, so that between looking for income and protecting oneself from spreading virus by staying at home is compatible with each other. This study was conducted between September and December 2020 and is located in the city of Makassar. Makassar was chosen because digital business grew significantly. Based on data from the Central Statistics Agency (BPS), the economy in the Eastern part of Indonesia (KTI) grew by an average of 8%, especially during the pandemic. There are seven participants who participated in this study who are varied based on age, occupation. Each informant is a user of one of the digital business platforms, namely VTube, Jempol Preneur, and Goins. The study shows that digital business is one type of business by utilizing digital devices such as gadgets (mobile phones and laptops) and internet networks. Every digital business is now has a digital platform and has its own way of managing, as well as different advantages for its consumers. There are so many platforms that are engaged in digital business because it can be done easily, with a simple way of working, with the promise of a pretty lucrative income, and can be done anywhere. This fits perfectly with the Covid-19 pandemic situation where people stay at home. VTube, Jempol Preneur, and Goins are three applications that each have their own specifications and how they work. Vtube and Goins are digital platforms engaged in advertising, while Jempol Preneur is a platform digital business on online shop. Although there are similarities between the three, that is, making money even though each has its own variant. The income of VTube users depends on what users achieve by watching ads. In the application system of the Jempol Preneur, one must be a member to be able to run an online shop. As members, they not only choose the type and promote the goods that have been provided by the application, but this can also be run without capital (dropship), or with personal capital (reseller). Additional income can also be obtained through the sale of the Jempol Preneur license. The more licenses sold, the more income they can earned. Meanwhile, in Goins, users are supposed to carry out a mission by liking and watching advertising videos on the Instagram application. The more people who are invited to join, the more income is earned. However, despite the advantages that each application has, each has its drawbacks. If Jempol Preneur already has legality, then VTube and Goins are under construction, which shows that the legality of the two is not yet clear and this is related to the basis of the business being run. For this reason, users who have already run this business must be prepared to bear the risks, such as no return of money at all and the lack of clarity from the parties concerned. Another aspect that is considered a drawback of Jempol Preneur is the obligation to pay a registration fee while VTube and Goins do not require it.